Developing Nickel/Graphene Nano Sheets as an alternative primary battery anode - Siburian, Rikson; Paiman, Suriati; Hutagalung, Fajar; Ali, Ab Malik Marwan; Simatupang, Lisnawaty; Goei, Ronn; Rusop, Mohamad Mahmood (Elsevier, 2022)
In this paper, we report the development of Nickel (Ni)/Graphene Nano Sheets (GNS) as a primary battery anode. The research focuses on the effect of Ni particle sizes on the performance of Ni/GNS anode. GNS and Ni/GNS (Ni wt% from 10 to 40%) are synthesized using the modified Hummers and impregnation method. We employed the use of commercial Zn-plate as an anode reference material. The materials are characterized with XRD, EDX, SEM, TEM and electrical conductivity meter. The XRD spectra of Ni-GNS have the broad and weak peaks at 2θ = 26.77 and 44.55° identified as C (002) and Ni (111), respectively. The XRD data is consistent with data obtained from EDX analysis which showed the presence of C and Ni at 0.277 and 7.472 keV respectively. The smallest Ni particle sizes of 23.4 nm was synthesized from Ni(20%)/GNS, Interestingly, the small particle size of Ni may improve the electrical conductivity of Ni/GNS. We found that Ni(20%)/GNS (62.2 μS/cm2) has a higher electrical conductivity value than GNS (61.4 μS/cm2) with commercial primary battery anodes Zn plate showing electrical conductivities of 35 μS/cm2. We therefore proposed the potential of Ni/GNS to be developed as alternative materials for primary battery anode.